Generalizations of Levinson-type inequalities via new Green functions and Hermite interpolating polynomial - Awais Rasheed; Khuram Ali Khan; Josip Pečarić; Ðilda Pečarić (Journal of Inequalities and Applications, 2024)
Abstract In this study, Levinson-type inequalities for the class of n-convex ( n ≥ 3 $n ≥ 3$ ) functions are generalized using new Green functions and the Hermite interpolating polynomial involving two types of data points. Some estimations for novel functionals are derived using f-divergence. Furthermore, different inequalities involving Shannon entropies are presented.